2008
DOI: 10.1590/s0102-695x2008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites isolated from Richardia brasiliensis Gomes (Rubiaceae)

Abstract: RESUMO: "Metabólitos secundários isolados de Richardia brasiliensis Gomes (Rubiaceae)".A família Rubiaceae compreende cerca de 637 gêneros e aproximadamente 10700 espécies, ocorrendo essencialmente nas regiões tropicais do Brasil. Richardia brasiliensis Gomes, popularmente conhecida por "poaia branca", é uma planta nativa da região sul do Brasil, utilizada na medicina popular como anti-emética e no tratamento de diabetes. Este trabalho reporta o isolamento e identifi cação estrutural de um fl avonóide glicosil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…The development of agronomic techniques aiming at maximizing medicinal, aromatic, flavouring, and ornamental species cultivation is a way of assuring raw material regular supply, controlling factors that could influence its phytochemical and pharmacological quality (LOURENZANI et al, 2004;PINTO et al, 2008;CHAGAS et al, 2011). However, studies aiming at maximizing the production of basil and other herbs are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The development of agronomic techniques aiming at maximizing medicinal, aromatic, flavouring, and ornamental species cultivation is a way of assuring raw material regular supply, controlling factors that could influence its phytochemical and pharmacological quality (LOURENZANI et al, 2004;PINTO et al, 2008;CHAGAS et al, 2011). However, studies aiming at maximizing the production of basil and other herbs are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…There are no reports regarding the total phenolis and total flavonoid content in Spermacoce species. The Rubiaceae family is known for the production of alkaloids, iridoids, and anthraquinones (YOUNG et al, 1996), and flavonoids have been isolated from species of this family (LOPES et al, 2004, CARDOSO et al, 2005PINTO et al, 2008). Noiarsa et al (2006) identified 18 substances from the aerial parts of Spermacoce laevis Roxb.…”
Section: Resultsmentioning
confidence: 99%
“…The results are good agreement with R. grandiflora which revealed the presence of two phenolic compounds, mmethoxy-p-hydroxybenzoic acid, hydroxybenzoic acid, two steroids in the mixture (β-sitosterol and stigmasterol) and chlorophyll derivative (pheophytin a). The phytochemicals investigation performed with R. brasiliensis revealed it had different classes of metabolites like coumarins, flavonoids, triterpenes, sterols and phenolic acids (Pinto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%